Association of Exposure to Cattle with Self-Reported History of TB Among Dairy Workers. (July 2021) - Rodriguez, Anabel; Douphrate, David I.; Hagevoort, Robert; Cienega, Leeroy; Gimeno Ruiz de Porras, David; Perez, Adriana; Nonnenmann, Matthew
Background: Mycobacterium bovis (bTB) is a potential health hazard to dairy workers. This study uses the One Health wholistic framework for examining bovine tuberculosis (TB) and its relationship to human health. This approach can help bridge surveillance data gaps and contribute to disease control and prevention programs for dairy farm workers, cattle, and the environment. The primary objective of this study was to compare the self-reported history of TB among dairy workers in Bailey County, Texas, with occupational categories of risk and exposure to TB. Methods: A cross-sectional study was conducted among dairy workers. Job positions were used as a proxy for exposure to cattle—high and medium/low. We employed bivariate analyses to examine differences between groups using both the chi-square test and the nonparametric Kruskal–Wallis test. Results: Of the 293 dairy workers invited, 77.0% ( n = 225) participated. No statistically significant associations were found between job categories and reported history of TB exposure. Workers in the high group were younger, Guatemalan males with lower levels of formal education, more likely to be single with no children, and cohabitating with coworkers compared with the medium/low group. Conclusion/Application to Practice: Self-reported TB history among dairy workers is an imprecise measure of being previously diagnosed with TB. Dairy workers at risk for occupationally acquired TB could be tested for TB before employment and tested periodically thereafter, and more expeditiously treated if a positive test is obtained. Future studies should focus on the feasibility of offering on-farm health services, such as TB screening.